Analysis of the Water Quality of the Buluh River as a Source of Clean Water in Kutai Kartanegara Regency, East Kalimantan Province - Christopaul Pala'langan Toding Layuk; Andi Gita Tenri Sumpala; Fachruddin Azwari; Christine Elia Benedicta; Marta Ekawati Siahaya; Kemala Hadidjah; Adi Supriadi; Arini Rajab (Politeknik Pertanian Negeri Samarinda, 2025)
Water is one of the most essential resources in daily life. One of the main water sources used to meet the needs of the people of East Kalimantan is the Buluh River. This study aims to analyze the water quality of the Buluh River based on physical, chemical, and microbiological parameters, in accordance with the river water quality standards outlined in the Indonesian Ministerial Regulation Number 22 of 2021. It also evaluates differences in water quality between two locations, namely the upstream and downstream sections of the Buluh River. The parameters analyzed include pH, Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Coliform. Data were collected through surveys and laboratory analyses. The results show that all parameters, including pH, TSS, BOD, COD, and Total Coliform, remain within the specified limits in both the upstream and downstream sections of the river. These findings indicate that the watershed ecosystem of the Buluh River is still well preserved. Collaboration among all stakeholders is essential to maintaining the river’s water quality by protecting the Buluh River watershed ecosystem.